RESTRUCTURING OF TOWN-FORMING ORGANIZATIONS: HOUSING AND UTILITY ASPECT - А. N. Ryahovskaya; S. Е. Кovan; О. G. Kryukova (Стратегические решения и риск-менеджмент, 2014)
The most important direction of improving of financial stability of town-forming organizations in non-diversified towns is restructuring. A set of measures is implemented during restructuring in order to improve the effectiveness of using property, a property complex, to create appropriate conditions for business, the reforming of structural subdivisions, a system of control, is carried out, as well as debt restructuring. However, restructuring in the form of separation of “independent” business units in non-core and inefficient activities, which are technologically connected with the main production of a town-forming enterprise, is inefficient, because in fact they cannot operate independently and, consequently, become a serious problem for the economy of monotowns.